BRAF mutation and its inhibitors in sarcoma treatment. (31st May 2020) - Liu, Haotian; Nazmun, Nahar; Hassan, Shafat; Liu, Xinyue; Yang, Jilong
Abstract: The mitogen‐activated protein kinase ( MAPK ) signaling pathway plays a significant role in mediating cellular physiological activities, such as proliferation, differentiation, apoptosis, and senescence. This signaling pathway is composed of several major proto‐oncogenes of RAS/RAF/MEK/ERK, among which the BRAF proto‐oncogene, as one of the three members of the RAF family, has a higher mutation rate than ARAF and CRAF and has attracted extensive attention. Regarding the BRAF mutation, approximately 95% of BRAF mutations belong to the BRAF V600E mutation, which can enhance the expression of the MAPK signaling pathway and is thus related to the occurrence and development of various malignant tumors and has been successfully identified as a therapeutic target. Moreover, drug resistance to BRAF inhibitor treatment also appears to be an important issue. Considering the successful use of BRAF inhibitors in melanoma, we provide a brief overview of the BRAF mutations, including their basic structures and activation mechanisms, and the new classification method for BRAF mutations. Most importantly, we summarize the results of BRAF inhibitor treatment in different sarcomas. To overcome drug resistance to BRAF inhibitor treatment, we also outline the different mechanisms of drug resistance to BRAF inhibitor treatment and introduce the combination strategy of BRAF inhibitors with other targeted therapies. Abstract : BRAF structures and their activation mechanisms.